Pengaruh Komisaris Independen dan Kepemilikan Insttitusional terhadap Real Earnings Management yang dimoderasi oleh Leverage Keuangan - Riska Bunga Rosmalia Putri (Fakultas Ekonomi dan Bisnis, 2026)
Agency theory views independent commissioners and institutional ownership as monitoring mechanisms intended to limit managerial opportunistic behavior arising from information asymmetry. However, prior studies have reported inconsistent findings regarding their effectiveness in constraining real earnings management, raising questions about whether these governance mechanisms function effectively or whether other factors may strengthen or weaken their influence. One factor suspected to influence this relationship is pressure arising from debt covenant compliance and the risk of covenant violations. Therefore, this study aims to examine the effect of independent commissioners and institutional ownership on real earnings management. This study focuses on technology sector firms due to their strong dependence on external financing and their exposure to the tech winter phenomenon since 2022, which has been characterized by significant declines in funding and innovation activities. Using a purposive sampling method, the study obtains 100 firm-year observations, which are analyzed using moderated regression analysis complemented by robustness testing. The regression results indicate that independent commissioners positively affect real earnings management, whereas institutional ownership has no significant effect. Furthermore, financial leverage strengthens the positive effect of independent commissioners on real earnings management, but does not moderate the relationship between institutional ownership and real earnings management.
:: Finalisasi file repositori 21 Juli 2026_Kurnadi
Keywords: independence commissioner; institutional ownership; real earnings management; leverage